High precision assembly test technology for space high reliability thermoelectric refrigeration system. Issue 1 (1st April 2022) - Liu, Xin; Zhao, Benhua; Li, Rongjun; Xiao, Meng; Wang, Shuai; Zhang, Bin; Fan, Yufeng
Abstract: Space Thermoelectric cooler is a key component of cryogenic equipment, which is used for high efficiency refrigeration of spacecraft in orbit. Its assembly state directly determines the refrigeration effect and service life. At the same time, it is characterized by high brittleness and low strength. In the assembly to low temperature equipment, thermoelectric cooler is required to be closely connected with internal and external components to achieve seamless connection and efficient heat transfer. At the same time, it is necessary to prevent the damage caused by large compressive stress caused by excessive assembly load, so as to meet the purpose of long life, high reliability and stable operation. The stiffness curve of thermoelectric refrigerator was obtained by measuring the component displacement when the pressure was applied under the simulated thermoelectric refrigerator assembly state, which was used as the guiding parameter to guide the thermoelectric refrigerator assembly. Meanwhile, the damage of thermoelectric refrigerator under different pressure loads was checked. Explore the variation law of displacement under different preload of refrigeration components. Finally, the high precision assembly is realized by unified combination of thermoelectric refrigerator and structural components of refrigeration assembly to meet the requirements of high efficiency, high reliability and long life refrigeration of space cryogenic equipment.